Evaluation of BHK21 cell-line adapted Newcastle disease vaccine - REDDY, G S; SRINIVASAN, V A (The Indian Journal of Animal Sciences, 2013)
Lasota strain of Newcastle disease virus was successfully adapted to BHK21 cell-culture. BHK21 cell-culture adapted virus showed reduced virus infectivity. MDT and HA with chicken and equine RBC and elevated ICPI when compared with Lasota virus of chick embryo origin. Thermostability of the virus was unaffected. Serological response and challenge test results of the chicks vaccinated with BHK21-adapted vaccine showed encouraging results.